ACCUMULATION OF COBALT IN THE ORGANISM OF FRESHWATER FISH DUE TO INCREASED CONTENT IN WATER - Markiv, V.S.; Khomenchuk, V.O.; Kurant, V.Z. (Reports of the National Academy of Sciences of Ukraine, 2024)
The peculiarities of the quantitative accumulation of cobalt in the body of crucian carp and pike at different concentrations in the surrounding water environment were studied. The relationship between the metal content in water and its accumulation in the gills, liver, and skeletal muscles was established. Elevated concentrations of cobalt in the aquatic environment (0.1 and 0.25 mg/dm3) primarily lead to the accumulation of the metal in the tissues of the studied fish species. A more pronounced increase in this indicator is observed with a concentration of 0.25 mg/ dm3 of the metal in the water. The degree of cobalt accumulation in fish tissues follows a specific order: liver, muscles, gills.